Kontribusi Daya Ledak `Otot Tungkai Terhadap Kemampuan Tendangan Sabit Atlet Pencak Silat Tapak `Suci - Nofendri, Dendi; Maidarman, Maidarman; Arwandi, John; Haryanto, Jeki; Yendrizal, Yendrizal; oktavianus, irfan (Universitas Negeri Padang, 2023)
The problem in this research is the low ability of the athletes of the tapak Suci of the pencak silat kick because the explosive power of the muscles affects the ability of the sabit kick. This study aims to determine the contribution of leg muscle explosive power to the crescent ability of tapak Suci pencak silat athletes. This type of research is correlational. The population in this study were all students of the tapak Suci pencak silat who were still actively participating in the training as many as 27 people. The sampling technique used purposive sampling technique with a total sample of 15 people. The leg muscle explosive power data were taken using the standing broad jump test and measuring the ability of the sabit kick was used the sabit kick ability test. The data analysis technique used product moment correlation analysis. The results of the study obtained correlation data r count 0.9191> r table 0.514 (the research hypothesis was accepted) which indicated a significant relationship between leg muscle explosive power and sickle kick ability at a significant level of 0.05α. This means that the relationship between the explosive power of the leg muscles is strong and unidirectional. With t count = 8.409> t table 1.753. then the proposed work hypothesis (Ha) can be accepted. Furthermore, the determination value of the data analysis results (r2) is 0.8447. This means that the explosive power of the leg muscles as an independent variable can contribute 84.47% to the dependent variable, namely the ability to sabit sickle.